Parental coaching in football - Beckmann-Waldenmayer, D. (Football Psychology - From Theory to Practice, 2019)
It is acknowledged that parents play an essential role in the life of young football players. Therefore, they must be integrated into developmental systems in football. Parents` behaviour is sometimes not appropriate and can even be detrimental to the performance and personality development of young athletes. Most often, this is due to a lack of knowledge on how best to support their child in this context. Parental coaching aims at providing parents with knowledge about children`s psychological needs and age-related skill development and how best to support their children. This is addressed from a systemic perspective that attempts to incorporate the different systems interacting in a young player`s development such as football, school, and family. Based on current scientific research and practical experience successful parental coaching interventions are described.